Rope Jumping As a Medium for Developing Gross Motor Skills in Children Aged 5–6 Years - Yenneka Sandra; Mutia Farina (Indonesian Journal of Early Childhood Education Studies, 2026)
Gross motor development is a fundamental aspect of early childhood education because it enables children to perform essential movements such as jumping, running, balancing, and coordinating body movements. Previous studies have demonstrated that rope-jumping activities can improve children's gross motor skills. However, limited research has examined how these skills develop progressively through systematic classroom action cycles. This study aimed to investigate the effectiveness of the traditional rope-jumping game in improving the gross motor skills of children aged 5–6 years through Classroom Action Research (CAR). The study was conducted in two action cycles involving 13 children at TK Aisyiyah Padang City. Data were collected using an observation sheet assessing large muscle strength, agility, movement coordination, movement accuracy, and active participation. The findings showed that the proportion of children achieving the categories of Developing as Expected (BSH) and Very Well Developed (BSB) increased from 61.54% in Cycle I to 100% in Cycle II after improvements were made to the learning activities. These findings indicate that the traditional rope-jumping game provides systematic and developmentally appropriate physical stimulation that effectively enhances gross motor skills among children aged 5–6 years.